Preparation of nanocrystalline MgNb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Letters, 2005)
A gel was formed when a aqueous solution of Mg(NO3)(2), NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, MgNb2O6 (MN). The formation of MN phase and lattice parameters were determined by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Electron microscopy; magnesium niobate; powders; X-ray diffraction